LIKUIDITAS PT INDOFOOD TAHUN 2015-2016 - Elfreda Aplonia Lau (LPPM University 17 Agustus 1945 Samarinda, 2018)
he rise of corporate activities encourages management to work smart and skilled in order to achieve the company's goals effectively and efficiently. Work effectively and efficiently will be unbalanced if not lonely with honesty. Company honesty can be reflected in its ability to meet short-term obligations commonly known as liquidityThis study aims to determine and analyze the liquidity of PT. Indofood in 2015 and 2016 and measure its growth. The theory used in this research is management accounting that focuses on liquidity, current ratio, quick ratio and cash ratio. The hypothesis of this research is hypothesis 1 to 3: Liquidity PT Indofood in 2015 and 2016 get the criteria of rule of thumb, and hypothesis 4 to 6: Liquidity of PT. Indofood in 2016 experienced growth. The analysis tool used is liquidity analysis measured from current ratio, quick ratio and cash ratio.The results showed that PT. Indofood is able to get its short term obligations in 2015 and 2016 and get the criteria of rule of thumb. Besides, the result of research shows that liquidity of PT. Indofood in 2016 experienced growth compared to liquidity in 2015. The results of this study can be used by stakeholders in deciding to invest in PT. Indofood or otherwise.